Inter Ethnic Relation at Pekanbaru City (A Case Study on Social Relation of Purwodadi Indah Residence) - Bahar, Aswandi; Maemunaty, Titi (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Pekanbaru is the capital of Riau Province. It has been a big city with the variety ethnics living there. The focus of the study was the problems of inter-ethnic relation in term of education, culture, religion, and language. The objective was to discover some phenomenon of cooperation and competition occurred at the city. Both would result integration and conflict at the residence. The approach methodology was by reviewing the previous research on concept of ethnic relation and social change. Qualitative naturalistic was the main method with interviewing and observing technique. The result described that the cooperation resulted integration and harmonization. Some competition resulted conflict in term of different understanding of religion, different level of education. While the relations tended to show a politeness, although the ethnical and cultural distinction. Mutual advising and informing were reducing conflict, and in other word, tolerance was established.